simplify the expression.

2(3x+4)−3(2x−2)+8(x−5

1 answer

To simplify the expression: 2(3x+4)−3(2x−2)+8(x−5), we can apply the distributive property and then combine like terms.

First, we distribute the 2, -3, and 8 across their respective parentheses:

2(3x+4) = 6x + 8,
-3(2x−2) = -6x + 6,
8(x−5) = 8x - 40.

Now, we can simplify the expression by combining like terms:

(6x + 8) - (6x - 6) + (8x - 40)
= 6x + 8 - 6x + 6 + 8x - 40
= (6x - 6x + 8x) + (8 + 6 - 40)
= 8x + 14 - 40
= 8x - 26.

Therefore, the simplified expression is 8x - 26.